Mrs Parman's Money Lottery According to an Accounting Scientiﬁc Perspective - Neni Kurnia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
This research aims to analyze Mrs Parman's money inheritance with a qualitative approach analyzed in the perspective of investment accounting, accounts receivable, time value for money, donations and income formed / owned. The population in this study was community residents in Lumajang Regency. This sampling using Purposive Sampling of residents in Dawuhan Lor Village. This study uses primary data sources and secondary data with observation, interview and documentation techniques. Another economical motive of most members of the inheritance is to make the legacy one of the instruments for obtaining investment funds such as for buying houses and precious metals, as a perspective of a receivable for the inheritance member who gets the lottery in the beginning because the person who gets the initial draw must pay the remaining amount of money from the month he has not paid, where payments must be made every month during the draw and that can be said to be due for payment of receivables bills, is a time value for money that is subject to nominal value at current money can experience a diﬀerence with the nominal value of money in the future value of the inheritance money obtained, is a contribution, namely in the inheritance of this Mrs Parman that one time the lottery is given to the manager of inheritance as a payment of services where it is in accounting science can be said as a contribution and is an instrument of income formed/hilarious because of the sluggishness of this inheritance, someone has recorded his income post even though money has not been received, because they have already carried out substantially activities that can hike the beneﬁts or noise inherent in the income, namely by engaging in an inheritance agreement and having made regular inheritance payments every month so that can be covered in a hobbled income criteria.